Code-Switching And Code-Mixing In Crazy Awesome Teachers - Ria Hendriani; Abdul Wahab; Karyawan Putraidi (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
This research investigates the phenomenon of code-switching and code-mixing in the Indonesian comedy film Crazy Awesome Teachers (Guru-Guru Gokil, 2020). The study focuses on how characters fluidly alternate between Bahasa Indonesia and English within their dialogues, reflecting complex sociolinguistic dynamics in Indonesia’s multilingual society. Using a qualitative content analysis approach, the research systematically examines selected scenes to identify patterns and functions of these language alternations. The findings reveal that code-switching and code-mixing in the film serve multiple communicative purposes. Firstly, they function as markers of social identity, allowing characters to position themselves within particular social groups, such as urban professionals or youth subcultures that favor bilingual speech. Secondly, the use of English lexical items and phrases often highlights professional expertise or educational background, reinforcing character roles as teachers or intellectuals. Thirdly, these alternations contribute significantly to the comedic effect, where unexpected language shifts create humor through incongruity or playful language play. Lastly, code-switching acts as a tool to foster group cohesion and solidarity among characters, signaling shared values or insider status. This study contributes to sociolinguistic scholarship by illustrating how contemporary Indonesian media reflects and negotiates the country’s evolving linguistic landscape, where English increasingly permeates everyday communication. It also sheds light on how bilingual practices in popular culture function beyond mere communication, encompassing identity construction, social positioning, and entertainment. By analyzing Crazy Awesome Teachers, this research underscores the importance of media texts as valuable sites for examining real-life language use and its social implications in a globalizing world.